Descriptive & Comparative Analysis of Labor IQ in Indonesia by Age, Education, and Provincial Domicile - Wikantiyoso, Bimo; Budisetyono, Gracia Amanda Sam; Setiawan, Alvin Benedict (Journal of The Community Development in Asia, 2024)
This study aims to determine the average IQ score of the Indonesian population in order to provide a more accurate basis for setting reasonable IQ targets in the employee recruitment process. The research method used is descriptive quantitative and comparative quantitative research with cross-sectional and convenience sampling methods. A pilot test of the instrument was conducted to ensure the reliability and validity of the scale used, and the results showed a high level of reliability (Cronbach's Alpha = 0.935). Descriptive analysis involved respondents' profiles, demographics, and IQ scores, while cross tabulation analysis was conducted for demographic variables such as gender, province, age, and education level against IQ scores. T-test results showed significant differences in IQ scores by age group, education level, and province. Although previous findings indicated a difference in average IQ between men and women, further analysis of this study's data showed that there was no significant difference in IQ scores between the sexes. These results highlight the complexity of factors that influence intelligence and challenge previous findings of IQ differences between men and women.